A review on bioaccumulation of ²³⁸u, ²³²th and ⁴⁰k by fish from selected regions - Muhammad Nur Rashidi Rosli (Pusat e-pembelajaran, UMS, 2021)
Natural radionuclides ²³⁸U, ²³²Th and ⁴⁰K have been discovered to be enhanced by a variety of marine organisms. The largest contributions to natural radioactivity in human food products are ²³⁸U, ²³²Th and ⁴⁰K, which can have a hazardous effect and play an essential role in humans. ²³⁸U, ²³²Th and ⁴⁰K concentrations, on the other hand, may vary depending on the sampling site and geographical region. Furthermore, literature reviews show that the concentrations of ²³⁸U, ²³²Th and ⁴⁰K organisms fluctuate depending on the species, dietary habits, physiological processes, body size, and seasonal changes. Several disputes between the different research papers were discovered throughout the literature review, and it was also recognised that some crucial components of the research were not well-documented and thus complete. As a result, additional investigation is required.